2021
DOI: 10.1016/j.jadohealth.2020.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Message Designs to Educate Adolescents About E-Cigarettes

Abstract: E-cigarette use is increasing among adolescents, despite potential harms. Social media messages are a promising way to educate youth about e-cigarettes, yet little is known about what message topics and formats will have beneficial impacts for message reception, reach, e-cigarette knowledge, and beliefs about harms. Methods: A national convenience sample of adolescents (n ¼ 928, aged 15e18 years) in high school was recruited for an online experiment. In October 2019, participants were randomized to view one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 37 publications
2
15
0
1
Order By: Relevance
“…Existing evidence supports the potential message efficacy of many of the frequently used themes found in this study, such as addiction and health risks of vaping ( England et al, 2021 , Noar et al, 2020 ). Adolescent and young adult e-cigarette users are less likely to believe that e-cigarette use will lead to addiction than non-users ( Lazard, 2021 , Rohde et al, 2018 , Rohde et al, 2021 ), and evidence suggests that addiction beliefs may be an important message target for vaping prevention campaigns ( Sangalang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing evidence supports the potential message efficacy of many of the frequently used themes found in this study, such as addiction and health risks of vaping ( England et al, 2021 , Noar et al, 2020 ). Adolescent and young adult e-cigarette users are less likely to believe that e-cigarette use will lead to addiction than non-users ( Lazard, 2021 , Rohde et al, 2018 , Rohde et al, 2021 ), and evidence suggests that addiction beliefs may be an important message target for vaping prevention campaigns ( Sangalang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of familiar chemicals in vaping prevention messages has been perceived as alarming and scary by teens ( Popova et al, 2021 ). Research suggests that the messaging strategy of focusing on chemicals with negative associations – such as formaldehyde – is a promising route for anti-vaping communicators hoping to elicit intended negative reactions among youth ( Lazard, 2021 , Roditis et al, 2020 , Wiseman et al, 2016 ). Still, quantitative evaluations of the efficacy of this approach are needed.…”
Section: Discussionmentioning
confidence: 99%
“…value of 0.03 (p<0.05). Similarly, The use of social media can improve adolescent knowledge and reduce their interest in using electronic cigarettes [21], [22]. The diseaseprevention campaign model provides important knowledge and induces willingness in adolescents to prevent a certain disease [23].…”
Section: Discussionmentioning
confidence: 99%
“…Social media platforms could also be leveraged when designing communication campaigns. Recent studies have found this approach promising, with social media messaging to educate youth about ECIGs leading to greater knowledge and beliefs about the dangers of vaping (Lazard, 2020).…”
Section: Discussionmentioning
confidence: 99%